INTEGRATION OF EDUCATION AND TRAINING IS A FACTOR OF ACHIEVING THE GOAL - Bozorova Zuhraxon (Journals Park Publishing, 2022)
The article talks about the integrality of education and training factors in the development of the young generation into a perfect person. In this, issues such as the family environment, the role of the community - the neighborhood will be covered, and attention will be paid to the problems related to preparing children for school.
Keywords: education of the young generation, integration of education and upbringing, family environment, the role of the neighborhood